Atom probe crystallography: Atomic-scale 3-D orientation mapping - Araullo-Peters, V; Gault, B; Shrestha, S; Yao, L; Moody, M; Ringer, S; Cairney, J (2012)
Understanding the relationship between atomic-scale structure and properties is becoming increasingly critical as microstructures are now tailored at the nanometre length scale. Here we demonstrate 3-D mapping of grain orientations through atom probe tomography by utilizing Hough transforms to extract the orientation of crystallographic directions. The disorientation across boundaries is also determined. We are now able to combine the powerful capability of atom probe for measuring the 3-D distribution of atoms with the new ability to provide accurate crystallographic information. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.